A study on validity of Indian Diabetes Risk Score for screening of diabetes mellitus among rural adult population at Rural Health Training Centre, Bhouri, under Department of Community Medicine - Namdev, Garima; Narkhede, Vinod (International Journal Of Community Medicine And Public Health, 2018)
Background: Diabetes mellitus is a major public health problem in India and many of them remain undetected throughout years. This scenario becomes worse in rural setup where limited heath care facilities are available. So, to detect risk of diabetes earlier, Indian diabetes risk score (IDRS) is to be used. There is also various socio demographic and anthropometric factors associated with the risk of occurring diabetes. The aims and objectives of the study were to study the validity of IDRS method as a screening tool in community as well as to determine the association of IDRS with socio demographic factors and body mass index (BMI). Methods: A cross sectional study was conducted on 270 study participants at rural health training centre (RHTC) for a period of around 7 months. All of them were being measured weight, height, waist circumference and calculated BMI. Along with it, they were categorized by applying IDRS method and measured blood sugar by glucometer also. Results: Out of 270 study subjects, 29% found to have high score. By applying IDRS, at score > 60, we found 32% sensitivity and 97% specificity. A statistically significant association of IDRS with age, gender, religion, socioeconomic status (SES), education, occupation and BMI was seen. Conclusions: In present study, IDRS method proved to be a good screening tool for detecting diabetes mellitus at rural set up with minimum cost.